Aquatic food quality and safety assessment methods - Shakila, R. Jeya.; Jeyasekaran, G. (Abingdon, Oxon ; Boc Raton, FL : CRC Press, 2021)
The book explains on the methods and procedures adopted for testing the quality and safety of aquatic food products. The analytical techniques available for testing the chemical constituents of aquatic food with separate chapters on the analysis of lipids, proteins, vitamins, and minerals are exhaustively given to determine their nutritional quality. The various methods for sensory, physical, biochemical and microbiological quality assessments of aquatic food are explicitly given with detailed protocols for easy adoption. Special chapters covering the chemical contaminants and permitted additives for residue monitoring are dealt, as they are important food safety requirements. This book will be very helpful for the food quality control technologists, food analysts, research scholars, and fisheries professionals as a holistic guide on a variety of testing procedures for facile adoption to meet the food safety and quality regulatory requirements. Note: T& F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
4.1. Analysis of protein classes -- 4.2. Separation of proteins based on solubility -- 4.2.1. Salting out process -- 4.2.2. Isoelectric precipitation process -- 4.2.3. Solvent fractionation process -- 4.2.4. Separation of contaminating proteins -- 4.3. Separation of proteins based on adsorption -- 4.3.1. Ion exchange chromatography -- 4.3.2. Affinity chromatography -- 4.4. Separation of proteins based on differences -- 4.4.1. Dialysis process -- 4.4.2. Ultrafiltration process -- 4.4.3. Gel filtration chromatography -- 4.4.4. Separation by electrophoresis -- 4.4.4.1. Non-denaturing Electrophoresis
OCLC-licensed vendor bibliographic record.
Keywords: Seafood -- Inspection; Seafood -- Quality control; Seafood industry -- Quality control; Seafood industry -- Safety measures; TECHNOLOGY / Food Science